Feasibility of transoral robotic‐assisted high‐resolution microendoscopic imaging of oropharyngeal squamous cell carcinoma. Issue 8 (18th June 2015) - Patsias, Alexis; Giraldez‐Rodriguez, Laureano; Polydorides, Alexandros D.; Richards‐Kortum, Rebecca; Anandasabapathy, Sharmila; Quang, Timothy; Sikora, Andrew G.; Miles, Brett; Andersen, Peter
Abstract Background Transoral robotic‐assisted oncologic surgery of the head and neck offers promising functional results. Nonetheless, the efficacy of oncologic surgery remains critically dependent on obtaining negative margins. We aimed to integrate a miniaturized high‐resolution fiber‐optic microendoscope (HRME), which provides real‐time histological assessment, with the da Vinci robotic system (Intuitive Surgical, Sunnyvale, CA). Methods Three patients undergoing transoral robotic surgery (TORS) were prospectively enrolled in this study. Optical imaging of the oropharynx was performed intraoperatively with the robotic‐assisted HRME. Results All patients underwent the procedure successfully with no complications. The HRME was successfully integrated with the da Vinci robotic system. Several sites of the oropharynx and associated malignancy were imaged, which correlated with the standard histopathological analysis. Conclusion Transoral robotic‐assisted HRME imaging of the oropharynx is a safe and technically feasible approach, providing a real‐time histological assessment and may serve as a valuable aid in oncologic surgery. © 2015 Wiley Periodicals, Inc. Head Neck37: E99–E102, 2015